2010
DOI: 10.1002/jbm.a.32818
|View full text |Cite
|
Sign up to set email alerts
|

Development of a three‐dimensional model for rapid evaluation of bone substitutes in vitro: Effect of the 45S5 bioglass

Abstract: The evaluation of innovative bone substitutes requires the development of an optimal model close to physiological conditions. An interesting alternative is the use of an immortalized cell line to construct multicellular spheroids, that is, three-dimensional (3D) cultures. In this study, a modified hanging drops method has resulted in the generation of spheroids with a well-established human fetal osteoblasts line (hFOB 1.19), and tests have been focused on the effect of 45S5 bioglass ionic dissolution products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(53 reference statements)
2
9
0
Order By: Relevance
“…In order to evaluate osteogenic cell behavior, immortalized fetal human osteoblasts (HFOB 1.19) were used in this study to mimic the in vivo scenario of interaction between implant surface and osteoblasts of healthy patients. The cellular morphology detected by microscopic assessment in our results is similar to that shown in other studies that also used HFOB 1.19 osteoblasts . The use of high resolution FEGSEM images allowed us to evaluate the cell morphological details such as spreading, cellular extensions (filopodia), and cell stretching onto the morphological structures of the test surfaces, as seen in Figure .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In order to evaluate osteogenic cell behavior, immortalized fetal human osteoblasts (HFOB 1.19) were used in this study to mimic the in vivo scenario of interaction between implant surface and osteoblasts of healthy patients. The cellular morphology detected by microscopic assessment in our results is similar to that shown in other studies that also used HFOB 1.19 osteoblasts . The use of high resolution FEGSEM images allowed us to evaluate the cell morphological details such as spreading, cellular extensions (filopodia), and cell stretching onto the morphological structures of the test surfaces, as seen in Figure .…”
Section: Discussionsupporting
confidence: 85%
“…Bioactive ceramic and glass‐ceramic particles are produced with defined characteristics of size, microstructure, chemical composition, and morphology to enhance bone integration and remodeling. Additionally, the mechanical properties of such ceramic materials are required for incorporation onto implant surfaces and subsurface . Adverse local tissue reactions have been observed after delamination of coating ceramic material…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alno et al 44 reported a similar differential effect of 45S5 BAG ionic dissolution products (1 w/v %-400 mm particle size) on the proliferation of human fetal osteoblasts cultured in 2D versus 3D spheroid culture. While they observed an increase in cell viability at 4 and 7 days for TCP cultured cells in contact with BAG conditioned medium, they report a significant decrease in cell viability for 3D cultured cells.…”
Section: Discussionmentioning
confidence: 77%
“…While they observed an increase in cell viability at 4 and 7 days for TCP cultured cells in contact with BAG conditioned medium, they report a significant decrease in cell viability for 3D cultured cells. 44 In native adult tissues, the microenvironment is characterized by greater cell-matrix interactions than cell-cell interactions. Therefore, spheroid cultures may not be the optimal set up to investigate BAG-cell interactions in 3D.…”
Section: Discussionmentioning
confidence: 99%